Readability of COVID-19 information by the Malaysian Ministry of Health - Ab Hamid, Ahmad Rauyani; Hashim, Muhammad Faizuddin; Ab Hassan, Nurliyana; Mhd Azhan, Norsadida (Universiti Sultan Zainal Abidin, Malaysia, 2020)
Background and Purpose: COVID-19 pandemic has caused catastrophe to global health. To collectively break the chain of infection, the Malaysian Ministry of Health (MMoH) disseminates information about COVID-19 through its official websites. Since they are intended for the general public, this crucial information must be easy to comprehend. A textual analysis was conducted to assess the readability level of COVID-19 information by the MMoH.